2015
DOI: 10.1039/c5ra02461g
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic-based controllable synthesis of rolled or rigid ultrathin gold nanoplates

Abstract: A microfluidic-based controllable seeded synthesis of rolled or rigid ultrathin gold nanoplates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…2d and e, micro droplets and multiphase ow can stably form in this chip, demonstrating multi-layer tape lithography quantied for microfabrication. The quantied stable micro-droplet formation inside this chip is also provided in ESI 2, † promising a wide range of microdroplet-applicant downstream elds such as cultivation of mammalian cells, 32 controllable synthesis of nanoplates, 33 and interactional assay of cell pairs, 34 etc.…”
Section: Y-channel Microchipmentioning
confidence: 98%
See 1 more Smart Citation
“…2d and e, micro droplets and multiphase ow can stably form in this chip, demonstrating multi-layer tape lithography quantied for microfabrication. The quantied stable micro-droplet formation inside this chip is also provided in ESI 2, † promising a wide range of microdroplet-applicant downstream elds such as cultivation of mammalian cells, 32 controllable synthesis of nanoplates, 33 and interactional assay of cell pairs, 34 etc.…”
Section: Y-channel Microchipmentioning
confidence: 98%
“…The quantified stable 80 micro-droplet formation inside this chip is also provided in supplementary material (ESI 2), promising a wide range of microdroplet-applicant downstream fields such as cultivation of mammalian cells, 32 controllable synthesis of nanoplates,33 and interactional assay of cell pairs,34 etc. a) The glass slide.…”
mentioning
confidence: 99%
“…Recently, different types of synthetic strategies based on microfluidic technology have been reported for the structural manipulation and functionalization of gold nanoparticles. Gold nano-leaflets with ultra-thin folded structures were synthesized at room temperature by using a three-channel microfluidic chip [ 43 ]. In this microfluidic synthesis, cetyltrimethylammonium chloride (CTAC) and sodium borohydride (NaBH 4 ) were used as protective and reducing agents, respectively.…”
Section: Progress Of Microfluidic Technology In the Synthesis Of Imentioning
confidence: 99%
“…Intriguingly, despite having an opposite charge, protein multilayers on AuNPs could stabilize and selflimit the cluster growth. 19,30 Self-limited supraparticles have also been synthesized through more complex synthetic routes: seed-mediated, 18,31,32 sacrificial substrate, 28 thermal, 23 and other methods. 33,34 Among them, Banin and colleagues found that semiconductor ZnSe nanoparticles could assemble spontaneously via a high-temperature synthetic route, which resulted in stable and monodisperse nanorod couples connected by twinning structures (Fig.…”
Section: Assembly Mechanism and Synthesismentioning
confidence: 99%